The mouth-throat models and inspiratory flow profiles in in vitro analytics of dry powder inhalers - Silen, Salla (My University, 2021)
Dry powder inhalers (DPI´s) are devices that operate by converting the powder into an aerosol form and release particles for the lung deposition. DPI´s can be characterized using aerodynamic particle size distribution (APSD) analyses. The aim of the research was to study how the APSD profile is affected when anatomical mouth throat models (MT-models) are used in the Next Generation Impactor (NGI) of DPI´s, and how the coating and size of the throat and the implementation of realistic flow profile in NGI analytics have affected the results. APSD was determined with the United States Pharmacopoeia (USP) throat and with coated and uncoated MT-models. A breathing simulator was connected to the setup to allow simulated healthy persons’ inhalation profile. The results showed that anatomical MT-models capture more of the emitted drug in the throat than the USP throat. This may indicate that the USP method underestimates the throat distribution in vivo. Results also indicated that the proportion remaining in the throat was higher in coated MT-models than uncoated ones. The smaller the size of the anatomical throat, the more drug particles were trapped in the throat. Results of fine particle dose (5 µm) were lower with the breathing simulator than without it. In conclusion, anatomical throat captured more drug particles than USP throat, consequently affecting the fine particle dose results. In addition, when the anatomical MT-models were used without the breathing simulator, the amount of particles was significantly higher than in MT-models with the breathing simulator.
Keywords: aerodynamic particle size distribution, dry powder inhaler, next generation impactor (NGI), inhalation flow profile, anatomical throats in NGI